Exploring the therapeutic mechanism of kaempferol in acute lung injury: Network pharmacology and experimental validation - Zhu-ying Zhou; Chen-xi Zhang; Xiu-ling Wei; Chuan-fu Wu; Da-gui Chen; Fu-sheng Shang; Chun-ming Jiang (Tissue and Cell, 2026)

Herbicidal activity mechanism and ecotoxicological study of novel triazolinone PPO inhibitors based on plant-derived allelochemical cinnamic acid - Li-Xia Zhao; Xian-Da Guo; Jia-Xiao Li; Yue-Li Zou; Shuang Gao; Ying Fu; Fei Ye (Pesticide Biochemistry and Physiology, 2026)

Continuous monitoring of moisture loss of beef, beetroot, and banana slices during microwave vacuum dehydration by using THz-TDS combined with transformer-based neural network - Ying Fu; Zhihang Zhang; Da-Wen Sun (Journal of Food Engineering, 2026)

Corrigendum to “A carboxymethyl chitosan/trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration” [Carbohydrate Polymers 354 (2025) 123305] - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2026)

Impacts of non-thermal pretreatments on banana slices during microwave vacuum dehydration using THz-TDS and NIR-HSI techniques - Ying Fu; Yuqiao Ren; Da-Wen Sun (Journal of Food Engineering, 2025)

Dynamic covalent synthesis of highly-crystalline and fully-cyclized aromatic COF as an artificial interphase layer toward stable lithium metal batteries - Wei Shao; Da Xu; Tiantian Wang; Huanghao Pan; Ying Liu; Xue Gao; Jiahuan Luo; Jing Wang; Zhong-Kun Li; Yao Guo; Huihui Zhao; Ning Fu; et al. (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan /trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2025)

Antibiotics ingestion altered the composition of gut microbes and affected the development and reproduction of the fall armyworm - Yan Fu; Luo-Yan Zhang; Qing-Yi Zhao; Da-Ying Fu; Hong Yu; Jin Xu; Song Yang (Journal of Pest Science, 2024)

Novel analysis of food processes by terahertz spectral imaging: A review of recent research findings - Ying Fu; Yuqiao Ren; Da-Wen Sun (Trends in Food Science & Technology, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Analyzing the effects of nonthermal pretreatments on the quality of microwave vacuum dehydrated beef using terahertz time-domain spectroscopy and near-infrared hyperspectral imaging - Yuqiao Ren; Ying Fu; Da-Wen Sun (Food Chemistry, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Cognitive changes are associated with increased blood-brain barrier leakage in non-brain metastases lung cancer patients - Da-Fu Zhang; Zhen-Hui Li; Zhi-Ping Zhang; Yin-Fu He; Bin-Li Shang; Xiu-Feng Xu; Ying-Ying Ding; Yu-Qi Cheng (Brain Imaging and Behavior, 2023)
To explore the relationship between cognitive function and blood–brain barrier leakage in non-brain metastasis lung cancer and healthy controls. 75 lung cancers without brain metastasis and 29 healthy controls matched with age, sex, and education were evaluated by cognitive assessment, and the Patlak pharmacokinetic model was used to calculate the average leakage in each brain region according to the automated anatomical labeling atlas. After that, the relationships between cognitive and blood–brain barrier leakage were evaluated. Compared with healthy controls, the leakage of bilateral temporal gyrus and whole brain gyrus were higher in patients with lung cancers ( P < 0.05), mainly in patients with advanced lung cancer ( P < 0.05), but not in patients with early lung cancer ( P > 0.05). The cognitive impairment of advanced lung cancers was mainly reflected in the damage of visuospatial/executive, and delayed recall. The left temporal gyrus with increased blood–brain barrier leakage showed negative correlations with delayed recall (r = -0.201, P = 0.042). An increase in blood–brain barrier leakage was found in non-brain metastases advanced lung cancers that corresponded to decreased delayed recall. With progression in lung cancer staging, blood–brain barrier shows higher leakage and may lead to brain metastases and lower cognitive development.

Spatially-explicit quantitative relationship for a potential PES mechanism: Cascade hydropower development in Yarlung Zangbo River Basin, China - Xiao-kang Zhu; Bin Fu; Ramon Felipe Bicudo Da Silva; Ying-man Guo; Chan-yuan Qin; Ting Feng; Hai-bing Yu; Kuang Xiao (Journal of Mountain Science, 2022)

Genetic diversity and structure of Oncomelania hupensis hupensis in two eco-epidemiological settings as revealed by the mitochondrial COX1 gene sequences - Jie-Ying Zhang; Man-Man Gu; Qiu-Fu Yu; Meng-Tao Sun; Hui-Ying Zou; Zhi-Jun Zhou; Da-Bing Lu (Molecular Biology Reports, 2022)

Investigation on the statistical characteristics of geoelectric field seismic anomalies in the North–South seismic belt of Chinese mainland - Hou Ze-Yu; An Zhang-Hui; Fan Ying-Ying; Tan Da-Cheng; Fu A-Long; Wei Lei (Acta Geophysica, 2021)

Identifying the sources of seasonal predictability based on climate memory analysis and variance decomposition - Da Nian; Naiming Yuan; Kairan Ying; Ge Liu; Zuntao Fu; Yanjun Qi; Christian L. E. Franzke (Climate Dynamics, 2020)

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua - Lu-yao Wang; Ying Zhang; Xue-qing Fu; Ting-ting Zhang; Jia-wei Ma; Li-da Zhang; Hong-mei Qian; Ke-xuan Tang; Shan Li; Jing-ya Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Architecture and development of a multi-stage Baiyun submarine slide complex in the Pearl River Canyon, northern South China Sea - Lei Wang; Shi-Guo Wu; Qing-Ping Li; Da-Wei Wang; Shao-Ying Fu (Geo-Marine Letters, 2014)

Sprout vacuum-infiltration: a simple and efficient agroinoculation method for virus-induced gene silencing in diverse solanaceous species - Hua-xue Yan; Da-qi Fu; Ben-zhong Zhu; Hai-ping Liu; Xiao-ying Shen; Yun-bo Luo (Plant Cell Reports, 2012)

The interaction between ubiquitin C-terminal hydrolase 37 and glucose-regulated protein 78 in hepatocellular carcinoma - Ying Fang; Jingui Mu; Yushui Ma; Duan Ma; Da Fu; Xizhong Shen (Molecular and Cellular Biochemistry, 2012)

Nicotine dependence and serum BDNF levels in male patients with schizophrenia - Xiang Yang Zhang; Mei Hong Xiu; Da Chun Chen; Fu De Yang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2010)

Gadolinium promoted proliferation and enhanced survival in human cervical carcinoma cells - Ying Zhang; Li-Juan Fu; Jin-Xia Li; Xiao-Gai Yang; Xiao-Da Yang; Kui Wang (BioMetals, 2009)

Vanadyl bisacetylacetonate induced G1/S cell cycle arrest via high-intensity ERK phosphorylation in HepG2 cells - Ying Fu; Qin Wang; Xiao-Gai Yang; Xiao-Da Yang; Kui Wang (JBIC Journal of Biological Inorganic Chemistry, 2008)